Germination Effect on Phenolic Composition and Antioxidants Activities of Faba Bean Cultivar - Rajhi, Imene; Mansour, Rim Ben; Mhadhbi, Haythem (Jour Med Resh and Health Sci, 2024)
Faba bean (Vicia faba L.) is considered as one of the most important legume crops in the world, and fourth on the level of pulses in importance, and it is being grown around the world as a food source of proteins, carbohydrates, fibers, and antioxidants. Germination process have an important effect on the amelioration of the nutritional proprieties of different seeds. The aim of this study was to evaluate the effect of germination on total phenolic content, flavonoids, tannins, total antioxidant capacity and DPPH scavenging activity for faba bean seeds. The characterization of the phenolic compounds was also achieved using HPLC-UV-DAD. The data showed that germination process ameliorate the total phenol and flavonoids contents and DPPH scavenging activity. On the other hand, tannins content and total antioxidant capacity were slightly increase during sprouting process. The result of the HPLC-UV-DAD analysis was also done for the raw and germinated ethanol extracts. One compound, the ascorbic acid (vitamin C) was detected in both samples.